Electronic Thermal Conductivity and Thermoelectric Performance of PbBi4Te7 - Quang, Tran Van (VNU Journal of Science: Mathematics - Physics; Vol 36 No 3, 2020)
Bismuth telluride and its related compounds are the state-of-the-art thermoelectric materials operating at room temperature. Bismuth telluride with Pb substituted, PbBi 4 Te 7 , has been found to be a new quasi-binary compound with an impressive high power factor. In this work, in the framework of density functional theory, we study the electronic thermal conductivity of the compound by employing the solution of Boltzmann Transport Equation in a constant relaxation-time approximation. The results show that the electronic thermal conductivity drastically increases with the increase of temperature and carrier concentration which have a detrimental effect on the thermoelectric performance. At a particular temperature, the competition between the thermal conductivity, the Seebeck coefficient and the electrical conductivity limits the thermoelectric figure of merit, ZT . The maximum ZT value of about 0.47 occurs at 520 K and at the carrier concentration of 5.0×10 19 cm -3 for n-type doping. This suggests that to maximize the thermoelectric performance of the compound, the carrier concentration must be carefully controlled and optimized whereas the best operating temperature is around 500 K.